Exemption of financial services in Value Added Tax - Biernacki, Krzysztof (Zwolnienie usług finansowych w podatku VAT, 2011)
Financial services are hard to tax by VAT because of the precise evaluation of the value added for tax-based purposes. The invoice-credit method with exemption dominates in the European Union. However, it results in too negative consequences, such as an additional tax burden for financial institutions. In order to cope with these problems, alternative methods of taxation of financial services were proposed. This article presents the invoice-credit method of the taxation of financial services in Poland and also provides comments in terms of the other method of taxation, such as services. The conclusions regard the possibility of applying other forms of taxation for financial services in Poland
Ekonomia = Economics, 2011, Nr 2 (14), s. 214-222
Keywords: financial services; taxation; VAT exemption